2017
DOI: 10.3390/ijms18020236
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Cancer Cells and the Tumour Microenvironment: The Role of the 5-Lipoxygenase Pathway

Abstract: 5-lipoxygenase is an enzyme responsible for the synthesis of a range of bioactive lipids signalling molecules known collectively as eicosanoids. 5-lipoxygenase metabolites such as 5-hydroxyeicosatetraenoic acid (5-HETE) and a number of leukotrienes are mostly derived from arachidonic acid and have been shown to be lipid mediators of inflammation in different pathological states including cancer. Upregulated 5-lipoxygenase expression and metabolite production is found in a number of cancer types and has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 191 publications
(262 reference statements)
3
66
1
1
Order By: Relevance
“…The results of this study are also supported by those of previous preclinical studies demonstrating that leukotriene inhibitors, a therapeutic category that includes the asthma medications montelukast (Singulair ® ), zafirlukast (Accolate ® ), zileuton (Zyflo ® ) and ubenimex (bestatin), inhibit tumors of the lung, esophagus and colon (26)(27)(28)(29). Finally, to the best of our knowledge, the only known human study to examine the effects of leukotriene inhibiting asthma medication found an overall reduced risk of cancer, in general, as well as of breast cancer, in particular; however, this study was limited to asthmatic patients (8).…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study are also supported by those of previous preclinical studies demonstrating that leukotriene inhibitors, a therapeutic category that includes the asthma medications montelukast (Singulair ® ), zafirlukast (Accolate ® ), zileuton (Zyflo ® ) and ubenimex (bestatin), inhibit tumors of the lung, esophagus and colon (26)(27)(28)(29). Finally, to the best of our knowledge, the only known human study to examine the effects of leukotriene inhibiting asthma medication found an overall reduced risk of cancer, in general, as well as of breast cancer, in particular; however, this study was limited to asthmatic patients (8).…”
Section: Discussionsupporting
confidence: 85%
“…BLT1 is a specific and high-affinity receptor for LTB 4 , whereas BLT2 exhibits a low affinity for LTB 4 and can bind other eicosanoids. Accumulating evidence indicates that most cancer cells express both BLT1 and BLT2 (44). However, the roles of each LTB 4 receptor in cancer development and progression remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that ALOX5 protein expression was associated with high-grade ECs and other adverse prognostic features including nodal metastasis. Indeed, while tumour ALOX5 expression promotes proliferation and survival [61][62][63][64], additional roles in stimulating angiogenesis [65], maintaining stemness [66], and promoting metastasis via immune effector cell interactions have also been reported [22,67,68]. In this study, ECs with high ALOX5 protein expression in combination with low HPGD were associated with a poorer prognosis than tumours with either feature alone.…”
Section: Discussionmentioning
confidence: 63%